The Role of Machiavellianism, Emotional Manipulation and Moral Foundations in Tax Avoidance - Hossein Esmaeili Komar Olia; Bahman Banimahd; Sina Kheradyar (Iranian Journal of Finance, 2019)
Tax avoidance is making use of legal loop holes to display an individual's financial situation as if it were lower than what it is in order to decrease the amount of income tax owed. Behavioral economics and taxation literature indicate that psychological factors can provide further insight on accountants' financial decisions. The literature claim that tax compliance can be influenced by an individual’s personality and beliefs. Therefore, in this research, the effects of psychological variables including Machiavellianism, emotional manipulation and moral foundations are examined on tax avoidance in accounting and finance professions. The aim of this study is to investigate the role of Machiavellianism and emotional manipulation as two negative attributes of human beings and moral foundations in tax avoidance in listed and unlisted firms. For this purpose, a sample consisting of 500 accountants and financial managers of listed and unlisted companies of Tehran stock exchange was selected. This study is an applied and descriptive survey. The hypotheses of the research have been analyzed by structural equation modeling using Lisrel software. The evidence of this study show that Machiavellianism has a positive and moral foundations have a negative effect on tax avoidance. But, this study doesn’t confirm any significant relation between emotional manipulation and tax avoidance. This paper also states that social and psychological variables  would  explain the tax avoidance phenomenon.